THE IMPORTANCE OF THE PHYSICS SUBJECT IN DEVELOPING PROFESSIONAL COMPETENCE - Charos Shakhriddinova daughter of Golibjon; Mamirova Sarvinoz daughter of Murod; Khodjayeva Diyora Zukhriddinovna (TADQIQOTLAR, 2025)
At present, through the initiatives of our national leader, significant reforms have been implemented  in  the  education  system,  creating  ample  opportunities  for  the further development of young people’s knowledge and worldview. The construction of preschools  in  remote  rural  areas,  the  modernization  of  schools  with  up- to-date technical  equipment,  the  opening  of  new  universities,  the  expansion  of  enrollment in higher education institutions, the creation of special opportunities for girls to study atuniversities, and the facilitation of study transfers for young people studying abroad all serve as clear examples of these developments. A natural question arises: To what extent are young people taking advantage of these opportunities? What is the current level of their knowledge? Can their worldview serve as the foundation for building our New Uzbekistan?